2015
DOI: 10.1002/dmrr.2641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea or tea extract on metabolic profiles in patients with type 2 diabetes mellitus: a meta‐analysis of ten randomized controlled trials

Abstract: As consumption of tea has been confirmed as a protective factor for type 2 diabetes mellitus (T2DM), it would be interesting to know if T2DM patients could benefit from tea. Because of small sample sizes and inconsistent results of previous studies, we performed this meta-analysis to reevaluate the effects of tea or tea extract on all available outcomes in patients with T2DM. We systematically searched electronic databases of PubMed, Cochrane Library and EMBASE to identify randomized controlled trials of tea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 42 publications
2
36
1
1
Order By: Relevance
“…Recent meta-analyses (Table S3) [138,139,140,141,142,143,144,145,146,147,148,149,150,151] suggest that the consumption of flavanol-containing tea and tea products could reduce total- and LDL-cholesterol as well as body mass index (BMI) and waist circumference (WC), while chocolate and cocoa flavanols also appear to regulate blood lipid levels. Nonetheless, the results of these analyses are inconsistent, partly due to the large heterogeneity of the clinical trials included.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses (Table S3) [138,139,140,141,142,143,144,145,146,147,148,149,150,151] suggest that the consumption of flavanol-containing tea and tea products could reduce total- and LDL-cholesterol as well as body mass index (BMI) and waist circumference (WC), while chocolate and cocoa flavanols also appear to regulate blood lipid levels. Nonetheless, the results of these analyses are inconsistent, partly due to the large heterogeneity of the clinical trials included.…”
Section: Discussionmentioning
confidence: 99%
“…275, 276 Yet, controlled trials of tea have not identified robust benefits on markers of glucose-insulin homeostasis. 277, 278 However, in meta-analyses of trials, green tea, black tea, and herbal roselle tea each modestly lower BP; 279-281 while green and black tea, but not herbal roselle tea, also lower LDL-cholesterol. 282-284 …”
Section: Foods and Cardiometabolic Healthmentioning
confidence: 99%
“…In db/db mice, a diabetes model, dietary EGCG was found to prevent the progression of glucose intolerance . Many epidemiological studies and short‐term randomized controlled trials (RCT) also showed an association between tea or catechin consumption and lower incidence of metabolic syndrome and diabetes, even though the results are not conclusive . In most studies, the beneficial effects were observed in individuals consuming three to four cups of tea (or 600–900 mg of tea catechins) or more daily.…”
Section: Introductionmentioning
confidence: 99%